Engineering Cytochrome P450BM3 Enzymes for Direct Nitration of Unsaturated Hydrocarbons. Issue 13 (6th February 2023) - Wang, Xiling; Lin, Xiaodan; Jiang, Yiping; Qin, Xiangquan; Ma, Nana; Yao, Fuquan; Dong, Sheng; Liu, Chuanfei; Feng, Yingang; Jin, Longyi; Xian, Mo; Cong, Zhiqi
Abstract: Applications of the peroxidase activity of cytochrome P450 enzymes in synthetic chemistry remain largely unexplored. We present herein a protein engineering strategy to increase cytochrome P450BM3 peroxidase activity for the direct nitration of aromatic compounds and terminal aryl‐substituted olefins in the presence of a dual‐functional small molecule (DFSM). Site‐directed mutations of key active‐site residues allowed the efficient regulation of steric effects to limit substrate access and, thus, a significant decrease in monooxygenation activity and increase in peroxidase activity. Nitration of several phenol and aniline compounds also yielded ortho ‐ and para ‐nitration products with moderate‐to‐high total turnover numbers. Besides direct aromatic nitration by P450 variants using nitrite as a nitrating agent, we also demonstrated the use of the DFSM‐facilitated P450 peroxidase system for the nitration of the vinyl group of styrene and its derivatives. Abstract : The peroxidase activity of a dual‐functional small‐molecule (DFSM)‐facilitated P450BM3‐H2 O2 system was drastically improved through mechanism‐guided protein engineering for the P450‐mediated direct nitration of phenols, anilines, and styrenes using nitrite as the nitrating agent. Co‐crystal structures revealed the crucial role of the steric effect introduced by site‐directed mutations of proximal residues in the regulation of substrate access.